The use of Digital Educational Resources in the Process of Teaching and Learning in Pandemic by COVID-19 - Pocinho, Ricardo (2021)
The Coronavirus advance is forcing schools and universities to revise their teaching methodologies. With the closure of the institutions, thousands of teachers and millions of students will have to find new ways of teaching and learning overnight, which will be a huge challenge. We cannot expect everyone to suddenly adapt to these new times. We are aware of the numerous Internet connection problems, but it is a great time to reinvent ourselves and build the courage to test the use of technological tools already available to structure alternatives in the distance education format. Thinking outside the box can help mitigate the momentary problem, as well as collaborate to strengthen digital culture and move towards a new education.The good news is that many teachers have been putting aside prejudices and are being resilient, seeking to understand the potential of available resources, not shying away from seeking and implementing technological solutions that before the virus were seen as secondary and have now become standard tools to teach synchronous and asynchronous classes, share content, correct assignments, answer questions and exchange knowledge. In the beginning, many activities that were previously carried out exclusively in person took a longer time when they started to be performed online. But as the virtual became the new real, students became more engaged and plunged headlong into relevant online learning experiences. Through applications and software, classes continued according to the school calendar.This study aimed to understand how teachers adapted to digital resources to face the limitations caused by the pandemic. It also intends to understand the impact of digital resources on the quality of teaching, as well as on motivation and academic success.